Investigation of the economic and ecological importance of the medicinal leech (Hirudo verbana) population in lake Manyas (Türkiye) - Ergün, Mustafa; Saglam, Naim; Pazar, Mehmet; Bulut, Cafer; Sezginer, Muhammed Mustafa; Çapkın, Kadir; Öztuna, İsmail Hakkı (Balıkesir Üniversitesi, 2026)
In this study, a population monitoring survey of medicinal leech (Hirudo verbana) in Lake Manyas was aimed. Between March-October 2024, population density and stock sizes were estimated by measuring the length, weight and condition factors of medicinal leeches at four different stations (Bereketli, Yenisığırcı, Ergili, Kocagöl). As a result of the study, the highest stock size was determined in August (38.908 individuals) and the lowest stock size was determined in October (1.998 individuals). The economic value of Lake Manyas medicinal leech was estimated as 2.221.450 TL and $55.000 in US dollars. Bereketli station stood out as the region with the highest biomass. The condition factor of individuals in Lake Manyas was found to be moderate in general, and the low proportion of broodstock individuals poses a threat to the sustainability of the population. Increasing environmental pressures around the lake, habitat loss and uncontrolled hunting pose a risk for the future of the populations. As a result of this research, periodical medicinal leeches hunting restrictions, stock-based hunting permits and encouragement of medicinal leech breeding are recommended for sustainable management. The findings provide scientific data for both the development of conservation strategies and the sustainability of medicinal leech populations.

Bu çalışmada, Manyas Gölü’nün tıbbi sülük (Hirudo verbana) popülasyon izleme araştırması amaçlanmıştır. 2024 yılı Mart-Ekim 2024 ayları arasında aylık olarak dört farklı istasyonda (Bereketli, Yenisığırcı, Ergili, Kocagöl) yapılan örneklemelerde, tıbbi sülüklerin boy, ağırlık ve kondisyon faktörleri ölçülerek popülasyon yoğunluğu ve stok büyüklükleri tahmin edilmiştir. Çalışma sonucunda en yüksek stok büyüklüğü Ağustos ayında (38.908 birey), en düşük stok büyüklüğü ise Ekim ayında (1.998 birey) tespit edilmiştir. Manyas Gölü tıbbi sülük ekonomik değeri ise 2.221.450 TL ve Amerikan doları cinsinden 55.000 $ olarak tahmin edilmiştir. Bereketli istasyonu, en yüksek biyokütleye sahip bölge olarak öne çıkmıştır. Manyas Gölü’ndeki bireylerin kondisyon faktörü genel olarak orta düzeyde bulunmuş; anaç birey oranının düşüklüğü, popülasyonun sürdürülebilirliği açısından tehdit oluşturmaktadır. Göl çevresinde artan çevresel baskılar, habitat kaybı ve kontrolsüz avcılık, popülasyonların geleceği için risk teşkil etmektedir. Araştırma sonucunda sürdürülebilir yönetim için dönemsel avcılık kısıtlamaları, stok temelli avcılık izinleri ve tıbbi sülük yetiştiriciliğinin teşvik edilmesi önerilmektedir. Elde edilen bulgular hem koruma stratejileri geliştirilmesi hem de tıbbi sülük popülasyonlarının sürdürülebilirliği için bilimsel bir veri sağlamaktadır.
Manyas gölü (Türkiye) tıbbi sülük (Hirudo verbana) popülasyonunun ekonomik ve ekolojik öneminin araştırılması
Keywords: Freshwater Ecology; Tatlı Su Ekolojisi